Marine ranching enhances ecosystem stability and biological carbon sequestration potential: insights from Ecopath with Ecosim model simulation of 30-year ecological path of a national marine ranching in China - Yan, Jiale; Chen, Yan; Cao, Yingkun; Sun, Jiamin; Wen, Bin; Gao, Xiaowei; Wang, Gang; Gong, Lixin; Liu, Huixin; Li, Qian; Liu, Xiujin; Zhang, Jiabo; et al. (Frontiers in Marine Science, 2025)
IntroductionMarine ranching is an effective marine ecosystem protection measure that not only helps protect marine resources, but also has an important carbon sink function.MethodsThis study took the Haizhidu marine ranching in the Bohai sea of China as the research object, constructed 20 functional groups in the area, and used the ecosystem model Ecopath with Ecosim (EwE) and stable isotopes (δ13C and δ15N) to model the system, evaluate the biological structure, energy transfer efficiency, and ecological carrying capacity (ECC) of different functional groups in the system, and calculate the carbon sequestration potential when shellfish reach ECC and the impact of marine ranching construction on system stability and maturity.Results and DiscussionThe results of the study on the characteristic parameters of the marine ranching system show that in the Haizhidu marine ranching ecosystem, the functional group with the highest biomass is the sediment detritus functional group (37.75 t/km2), followed by phytoplankton (21.40 t/km2), and the lowest is the other pelagic fishes (0.26 t/km2); the highest trophic level is the Platycephalus indicus (3.70), followed by the 3.43 of Sebastes schlegelii and cephalopods; the energy transfer efficiency is mainly concentrated in the trophic levels I and II. The simulation results of the shellfish ECC show that the ECC of shellfish in this system is 49.21 t/km2. When the system reaches this capacity, the carbon sequestration potential of shellfish is 12.44 t/km2, and the total carbon fixation of the system can increase by 12.90 t/km2. At the same time, the ecosystem showed a high degree of maturity and stability when the shellfish proliferated to the ECC.ConclusionIn general, the results show that in the process of marine ranching management, reasonable control of the number of shellfish can improve the stability of the system and increase its carbon sequestration capacity. The research results can provide a scientific reference for the ecological service function of marine ranching in the future and increase the carbon sequestration service function of marine ranching ecosystems.